Do children benefit from internet access? Experimental evidence from a developing country - Ofer Malamud; Santiago Cueto; Julian Cristia; Diether W. Beuermann (Inter-American Development Bank (IDB), 2018)
This paper provides experimental evidence for the impact of home internet access on a broad range of child outcomes in Peru. Children who were randomly chosen to receive laptops with high-speed internet access are compared with i) those who did not receive laptops and ii) those who only received laptops without internet. It is found that providing free internet access led to improved computer and internet proficiency relative to those without laptops and improved internet proficiency compared to those with laptops only. However, there were no significant effects of internet access on math and reading achievement, cognitive skills, self-esteem, teacher perceptions, or school grades when compared to either group. Reasons for the absence of impacts on these key outcomes are explored with survey questions, time-diaries, and computer logs.
Keywords: C93; I21; I28; 330; Internet access; Education; Academic achievement; Digital skills; Cognitive skills; Technology; Experimental; Internet; Internetnutzung; Schüler; Bildungsniveau; Experiment; Peru